Excellent long-term results of the Müller acetabular reinforcement ring in primary cup revision: A single-center study of 259 cases after a mean of 10 years' follow-up. (2nd November 2017) - Mueller Greber, Pascal; Manzoni, Isabella; Ochsner, Peter E; Ilchmann, Thomas; Zwicky, Lukas; Clauss, Martin
Abstract : Background and purpose — The original Müller acetabular reinforcement ring (ARR) was developed to be used for acetabular revisions with small cavitary and/or segmental defects or poor acetabular bone quality. Long-term data for this device are scarce. We therefore investigated long-term survival and radiographic outcome for revision total hip arthroplasty using the ARR. Patients and methods — Between October 1984 and December 2005, 259 primary acetabular revisions using an ARR were performed in 245 patients (259 hips). The mean follow-up time was 10 (0–27) years; 8 hips were lost to follow-up. The cumulative incidence for revision was calculated using a competing risk model. Radiographic assessment was performed for 90 hips with minimum 10 years' follow-up. It included evaluation of osteolysis, migration and loosening. Results — 16 ARRs were re-revised: 8 for aseptic loosening, 6 for infection, 1 for suspected infection, and 1 due to malpositioning of the cup. The cumulative re-revision rate for aseptic loosening of the ARR at 20 years was 3.7% (95% CI 1.7–6.8%). Assuming all patients lost to follow-up were revised for aseptic loosening, the re-revision rate at 20 years was 6.9% (95% CI 4.1–11%). The overall re-revision rate of the ARR for any reason at 20 years was 7.0% (95% CI 4.1–11%). 21 (23%) of the 90 radiographically examined ARR had radiographic changes: 12 showed isolated signs of osteolysis but were not loose; 9 were determined loose on follow-up, of which 5 were revised. Interpretation — Our data suggest that the long-term survival and radiographic results of the ARR in primary acetabular revision are excellent.